N-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical property and preparation method thereof
By introducing PFN-Br on PVA and CuCl2, using metal coordination and hydrophobic interactions, an n-type ionic thermoelectric hydrogel with high thermal potential and excellent mechanical properties was prepared, which solved the problems of low thermal potential and insufficient mechanical properties of existing n-type thermoelectric materials, and achieved efficient thermoelectric conversion and good mechanical properties of the materials in complex environments.
Patent Information
- Application Number
- CN202411964572.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
Among the existing ionic thermoelectric materials, n-type thermoelectric materials have fewer and generally lower thermoelectric potential than p-type thermoelectric materials, which limits the design of ultra-sensitive ion thermoelectric materials and the application of flexible devices. At the same time, the stability of the thermoelectric properties of ionic thermoelectric materials in complex working environments is insufficient.
Polyvinyl alcohol (PVA) is used as the polymer matrix to form copper ion coordination with copper chloride through metal coordination, and combined with the hydrophobic interaction of the water-soluble conjugated polymer PFN-Br, an n-type ionic thermoelectric hydrogel with high thermoelectric properties and excellent mechanical properties is prepared. The method includes mixing PVA, CuCl2 and PFN-Br in deionized water, freeze-thawing and dry annealing treatment, and finally fully swelling in deionized water to obtain an n-type ionic thermoelectric hydrogel.
The high thermal potential and excellent mechanical properties of n-type ionic thermoelectric hydrogels are achieved, making them an ideal material for wearable devices to provide thermoelectric conversion. The thermoelectric potential of the material reaches -21.5mV/K, the tensile strength reaches 10.3MPa, and the elongation of break is 276%, which significantly improves the thermoelectric and mechanical properties of the material.
Smart Images

Figure CN119775615A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of ionic thermoelectric materials, and in particular to an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties and a preparation method thereof. Background Art
[0002] With the rise of new energy and renewable energy, environmentally friendly energy such as wind energy, solar energy, and biomass energy has become the trend of energy development. In this context, thermoelectric materials, as an environmentally friendly energy conversion method, have great development potential.
[0003] Depending on the type of carrier, thermoelectric materials are divided into electronic thermoelectric (e-TE) and ionic thermoelectric (i-TE) materials. Among them, e-TE materials form a potential difference through electron or hole transport under a certain temperature difference. However, the available voltage that traditional electronic thermoelectric materials can generate is extremely low (usually at the μV / K level), which limits its development. In contrast, i-TE materials can generate millivolt-level open-circuit voltages within a low temperature range and have high flexibility and scalability. It is foreseeable that i-TE materials will become one of the most competitive candidates for thermoelectric conversion in wearable devices. i-TE materials are divided into two categories, one is i-TE materials based on thermoelectric effect, and the other is i-TE materials based on thermal diffusion effect (Soret effect). Among them, i-TE materials based on thermoelectric effect generate a potential difference by continuous oxidation and reduction under a certain temperature gradient; while i-TE materials based on Soret effect generate a potential difference by selective migration of ions under a certain temperature gradient. For i-TE materials, the thermoelectric potential S i It is one of its most important performance indicators. Based on previous reports, the thermoelectric potential of i-TE materials based on thermal diffusion effect is generally high. Thanks to the advantages of high thermoelectric potential, i-TE materials have been continuously developed.
[0004] Under a certain temperature gradient, the difference in thermoelectric mobility between anions and cations is the key to effectively improving the performance of ionic thermoelectrics. Although ionic thermoelectric materials and devices have developed rapidly in recent years, there are relatively few n-type thermoelectric materials among the i-TE materials reported so far, and their thermoelectric potential is generally lower than that of p-type thermoelectric materials, which has a great limitation on the design of ultra-sensitive ionic thermoelectric piles. In addition, the application of ionic thermoelectric materials as flexible devices in energy storage, power generation, etc. needs to face a relatively complex working environment, which requires ionic thermoelectric materials to maintain their thermoelectric properties under various conditions. Therefore, higher requirements are placed on hydrogels in terms of mechanical properties, thermal stability, etc. Based on this, it is of great significance to develop an ionic thermoelectric hydrogel that takes into account both thermoelectric properties and mechanical properties. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties and a preparation method thereof.
[0006] In a first aspect, the present invention provides a method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties, which is achieved through the following technical scheme.
[0007] A method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties comprises the following steps:
[0008] S1. Adding a water-soluble conjugated polymer, polyvinyl alcohol and a water-soluble metal salt to deionized water to obtain a mixed solution; wherein the mass ratio of polyvinyl alcohol, water-soluble metal salt and water-soluble conjugated polymer is 1:0.05:0.075~0.15;
[0009] S2. pouring the mixed solution obtained in step S1 into a mold and subjecting it to freeze-thaw treatment to obtain a freeze-thawed hydrogel;
[0010] S3. dry annealing the frozen-thawed hydrogel at 80-120°C for 10-110 minutes;
[0011] S4. The annealed hydrogel is placed in deionized water until fully swollen to obtain an n-type ionic thermoelectric hydrogel.
[0012] Furthermore, in step S1, the water-soluble metal salt is selected from one or more of sodium chloride, potassium chloride, copper chloride, and zinc chloride.
[0013] Preferably, in step S1, the water-soluble metal salt is cupric chloride.
[0014] Furthermore, in step S1, the water-soluble conjugated polymer is poly(9,9-bis(3'-(N,N dimethyl)-N ethylaminopropyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)) (abbreviated as PFN-Br).
[0015] Furthermore, in step S1, the molecular weight of the polyvinyl alcohol is 146,000-186,000.
[0016] Furthermore, in step S1, the mass ratio of polyvinyl alcohol, water-soluble metal salt and water-soluble conjugated polymer is 1:0.05:0.125.
[0017] Furthermore, in step S1, a water-soluble conjugated polymer, polyvinyl alcohol and a water-soluble metal salt are added to deionized water, stirred until the water-soluble conjugated polymer and the water-soluble metal salt are completely dissolved, and then stirred and heated in a water bath at 80-120° C. for 8 to 12 hours to obtain a mixed solution.
[0018] Furthermore, in step S2, the freeze-thaw treatment conditions are: freezing at -20 to -40°C for 10 to 14 hours and thawing at room temperature for 10 to 14 hours.
[0019] The core of the present invention is to improve the mechanical properties while improving the thermoelectric properties of the hydrogel. The Seebeck coefficient of the thermoelectric material is one of the indicators for intuitively evaluating the thermoelectric properties of the material. For the thermoelectric performance, it is extremely important to ensure a high Seebeck coefficient while having good mechanical properties for the application of thermoelectric materials, but this is also the difficulty faced in the preparation of thermoelectric materials.
[0020] By adopting the above technical scheme, the present invention uses polyvinyl alcohol (PVA) as a polymer matrix, and the hydroxyl groups on PVA and the copper ions on the copper chloride undergo metal coordination. On this basis, the introduction of PFN-Br causes the hydrophobic long chain of PVA to produce hydrophobic interaction with the main chain of PFN-Br, causing the bromide ions on the PFN-Br chain to fall off and move to the cold end together with the chloride ions in the copper chloride under the temperature gradient, thereby generating a high thermoelectric potential. In addition, the introduction of the dry annealing process not only improves the crystallinity of PVA, but also strengthens the internal hydrophobic interaction, thereby achieving the effect of synchronously improving the mechanical properties and thermoelectric properties of the material as a whole.
[0021] In a second aspect, the present invention provides an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties, which is achieved through the following technical solution.
[0022] An n-type ionic thermoelectric hydrogel prepared by the above preparation method.
[0023] In a third aspect, the present invention provides an application of an n-type ionic thermoelectric hydrogel having high thermoelectricity and excellent mechanical properties, which is achieved through the following technical solution.
[0024] An application of the above n-type ionic thermoelectric hydrogel in flexible electronic devices.
[0025] Furthermore, the electronic device includes a capacitor and a generator.
[0026] This application has the following beneficial effects.
[0027] (1) This application uses metal coordination and hydrophobic effect to synergistically improve ion thermoelectric potential
[0028] In the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel, the hydroxyl groups (-OH) on the PVA chains interact with the Cu 2+(CuCl2) metal coordination occurs, and the hydrophobic long chains on PVA and the main chain of PFN-Br form chain aggregation and entanglement through hydrophobic interaction. After the dry annealing process, the coordination effect is stabilized and the range of action between PVA and PFN-Br is strengthened. In this way, a high negative thermal potential of -21.5mV / K is achieved.
[0029] (2) The present application prepares an n-type ionic thermoelectric hydrogel with high thermoelectric potential
[0030] Among the ionic thermoelectric materials reported so far, n-type thermoelectric materials are relatively rare, and their thermoelectric potential is generally lower than that of p-type thermoelectric materials. This application successfully prepares n-type ionic thermoelectric hydrogels with high thermoelectric potential.
[0031] (3) The ionic thermoelectric hydrogel prepared in this application achieves a synergistic improvement in thermoelectric performance and mechanical properties
[0032] The PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel of the present invention has both high mechanical properties and thermoelectric properties. Its high thermoelectric potential and excellent mechanical properties make it an ideal candidate material for providing thermoelectric conversion in wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a preparation flow chart of the present invention;
[0034] Figure 2 It is the ionic thermoelectric mechanism of the present invention that is a synergistic effect of metal coordination and hydrophobic interaction;
[0035] Figure 3 The microscopic morphology of the ionic thermoelectric hydrogel prepared by dry annealing method in Example 1 of the present invention and Comparative Example 1 (among which, a. SEM image of PVA / CuCl2; b. SEM image of PVA / CuCl2 / PFN-Br);
[0036] Figure 4 It is a graph showing the mechanical properties of the ionic thermoelectric hydrogels prepared in the examples of the present invention and the comparative examples;
[0037] Figure 5 This is a graph showing the thermoelectric potential of the ionic thermoelectric hydrogel of the present invention;
[0038] Figure 6 This is a diagram showing the application results of the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel device prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The invention will be further described below with reference to the accompanying drawings and embodiments.
[0040] The PFN-Br used in the following examples of the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 889672-99-5.
[0041] Example 1
[0042] The PVA / 5%CuCl2 / 12.5%PFN-Br ionic thermoelectric hydrogel was prepared by dry annealing method, comprising the following steps:
[0043] (1) Preparation of PVA / CuCl2 / PFN-Br mixed solution
[0044] PFN-Br powder (0.625 g), CuCl2 particles (0.25 g) and PVA particles (5 g) were dissolved in 35 mL of deionized water and stirred until PFN-Br and CuCl2 were completely dissolved. The mixed solution was stirred and heated in a 100°C water bath for 12 hours to obtain a mixed solution of PVA / CuCl2 / PFN-Br.
[0045] (2) Freeze-thaw treatment
[0046] The PVA / CuCl2 / PFN-Br mixed solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA / CuCl2 / PFN-Br hydrogel.
[0047] (3) Dry annealing process
[0048] The freeze-thawed PVA / CuCl2 / PFN-Br hydrogel was dry annealed at 100°C for 90 minutes.
[0049] (4) Fully swollen
[0050] The annealed hydrogel is placed in deionized water until it is fully swollen, and the obtained product is the n-type ionic thermoelectric hydrogel PVA / 5%CuCl2 / 12.5%PFN-Br.
[0051] Example 2
[0052] The PVA / 5%CuCl2 / 7.5%PFN-Br ionic thermoelectric hydrogel was prepared by dry annealing method, comprising the following steps:
[0053] (1) Preparation of PVA / CuCl2 / PFN-Br mixed solution
[0054] PFN-Br powder (0.375 g), CuCl2 particles (0.25 g) and PVA particles (5 g) were dissolved in 35 mL of deionized water and stirred until PFN-Br and CuCl2 were completely dissolved. The mixed solution was stirred and heated in a 100°C water bath for 12 hours to obtain a mixed solution of PVA / CuCl2 / PFN-Br.
[0055] (2) Freeze-thaw treatment
[0056] The PVA / CuCl2 / PFN-Br mixed solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA / CuCl2 / PFN-Br hydrogel.
[0057] (3) Dry annealing process
[0058] The freeze-thawed PVA / CuCl2 / PFN-Br hydrogel was dry annealed at 100°C for 90 minutes.
[0059] (4) Fully swollen
[0060] The annealed hydrogel is placed in deionized water until it is fully swollen, and the obtained product is the n-type ionic thermoelectric hydrogel PVA / 5%CuCl2 / 7.5%PFN-Br.
[0061] Example 3
[0062] The PVA / 5%CuCl2 / 10%PFN-Br ionic thermoelectric hydrogel was prepared by dry annealing method, comprising the following steps:
[0063] (1) Preparation of PVA / CuCl2 / PFN-Br mixed solution
[0064] PFN-Br powder (0.5 g), CuCl2 particles (0.25 g) and PVA particles (5 g) were dissolved in 35 mL of deionized water and stirred until PFN-Br and CuCl2 were completely dissolved. The mixed solution was stirred and heated in a 100°C water bath for 12 hours to obtain a mixed solution of PVA / CuCl2 / PFN-Br.
[0065] (2) Freeze-thaw treatment
[0066] The PVA / CuCl2 / PFN-Br mixed solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA / CuCl2 / PFN-Br hydrogel.
[0067] (3) Dry annealing process
[0068] The freeze-thawed PVA / CuCl2 / PFN-Br hydrogel was dry annealed at 100°C for 90 minutes.
[0069] (4) Fully swollen
[0070] The annealed hydrogel is placed in deionized water until it is fully swollen, and the obtained product is the n-type ionic thermoelectric hydrogel PVA / 5%CuCl2 / 10%PFN-Br.
[0071] Example 4
[0072] The PVA / 5%CuCl2 / 15%PFN-Br ionic thermoelectric hydrogel was prepared by dry annealing method, comprising the following steps:
[0073] (1) Preparation of PVA / CuCl2 / PFN-Br mixed solution
[0074] PFN-Br powder (0.75 g), CuCl2 particles (0.25 g) and PVA particles (5 g) were dissolved in 35 mL of deionized water and stirred until PFN-Br and CuCl2 were completely dissolved. The mixed solution was stirred and heated in a 100°C water bath for 12 hours to obtain a mixed solution of PVA / CuCl2 / PFN-Br.
[0075] (2) Freeze-thaw treatment
[0076] The PVA / CuCl2 / PFN-Br mixed solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA / CuCl2 / PFN-Br hydrogel.
[0077] (3) Dry annealing process
[0078] The freeze-thawed PVA / CuCl2 / PFN-Br hydrogel was dry annealed at 100°C for 90 minutes.
[0079] (4) Fully swollen
[0080] The annealed hydrogel is placed in deionized water until it is fully swollen, and the obtained product is the n-type ionic thermoelectric hydrogel PVA / 5%CuCl2 / 15%PFN-Br.
[0081] Comparative Example 1
[0082] Preparation of PVA / CuCl2 Ionic Thermoelectric Hydrogel by Dry Annealing Method
[0083] The preparation process is different from Example 1 in that PFN-Br is not added, and the remaining steps and parameters are the same as those in Example 1.
[0084] like Figure 3 As shown in the scanning electron microscopy (SEM) of (a) and (b), PVA / CuCl2 hydrogel and PVA / CuCl2 / PFN-Br hydrogel present porous structures due to water evaporation after freeze drying. Compared with PVA / CuCl2 hydrogel, the pore size of PVA / CuCl2 / PFN-Br hydrogel is relatively small because of the hydrophobic interaction that forms a more compact hydrogel structure. This porous structure provides organized channels for ion migration in ionic thermoelectric hydrogels.
[0085] Comparative Example 2
[0086] The PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel is prepared by an air drying method, comprising the following steps:
[0087] (1) Preparation of PVA / CuCl2 / PFN-Br mixed solution
[0088] PFN-Br powder (0.625 g), CuCl2 particles (0.25 g) and PVA particles (5 g) were dissolved in 35 mL of deionized water and stirred until PFN-Br and CuCl2 were completely dissolved. The mixed solution was stirred and heated in a 100°C water bath for 12 hours to obtain a mixed solution of PVA / CuCl2 / PFN-Br.
[0089] (2) Freeze-thaw treatment
[0090] The PVA / CuCl2 / PFN-Br mixed solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA / CuCl2 / PFN-Br hydrogel.
[0091] (3) Fully swollen
[0092] The freeze-thawed PVA / CuCl2 / PFN-Br hydrogel obtained in step (2) is placed in deionized water until it is fully swollen to obtain the product PVA / CuCl2 / PFN-Br hydrogel.
[0093] Comparative Example 3
[0094] Preparation of PVA / CuCl2 Ionic Thermoelectric Hydrogel by Air Drying Method
[0095] During the preparation process, the difference from Comparative Example 2 is that PFN-Br is not added, and the remaining step parameters are the same as those of Comparative Example 2.
[0096] Comparative Example 4
[0097] The PVA / PFN-Br ionic thermoelectric hydrogel is prepared by dry annealing method, comprising the following steps:
[0098] (1) Preparation of PVA / PFN-Br mixed solution
[0099] PFN-Br powder (0.625 g) and PVA particles (5 g) were dissolved in 35 mL of deionized water and stirred until PFN-Br was completely dissolved. The mixed solution was stirred and heated in a 100° C. water bath for 12 hours to obtain a PVA / PFN-Br mixed solution.
[0100] (2) Freeze-thaw treatment
[0101] The PVA / PFN-Br mixed solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA / PFN-Br hydrogel.
[0102] (3) Dry annealing process
[0103] The freeze-thawed PVA / PFN-Br hydrogel was dry annealed at 100°C for 90 minutes.
[0104] (4) Fully swollen
[0105] The annealed hydrogel is placed in deionized water until it is fully swollen, and the obtained product is the n-type ionic thermoelectric hydrogel PVA / PFN-Br.
[0106] Comparative Example 5
[0107] Preparation of PVA / PFN-Br ionic thermoelectric hydrogel by air drying method
[0108] The preparation process is different from Comparative Example 4 in that no thermal annealing treatment is performed, and swelling is performed directly after the freeze-thawed hydrogel is obtained. The remaining step parameters are the same as those of Comparative Example 4.
[0109] Comparative Example 6
[0110] The PVA hydrogel is prepared by dry annealing method, comprising the following steps:
[0111] (1) Dissolve 5 g of PVA particles in 35 mL of deionized water and heat in a 100° C. water bath with stirring for 12 hours to obtain a PVA solution.
[0112] (2) Freeze-thaw treatment
[0113] The PVA solution obtained in step (1) was poured into a polytetrafluoroethylene mold, frozen at -40°C for 12 hours, and thawed at room temperature for 12 hours to obtain a freeze-thawed PVA hydrogel.
[0114] (3) Dry annealing process
[0115] The freeze-thawed PVA hydrogel was dry annealed at 100°C for 90 minutes.
[0116] (4) Fully swollen
[0117] The annealed hydrogel is placed in deionized water until it is fully swollen, and the obtained product is PVA hydrogel.
[0118] Comparative Example 7
[0119] Preparation of PVA hydrogel by air drying method
[0120] The preparation process is different from Comparative Example 6 in that no thermal annealing treatment is performed, and the freeze-thawed PVA hydrogel is directly swelled after being obtained, and the remaining step parameters are the same as those of Comparative Example 6.
[0121] Performance Testing
[0122] 1. Mechanical properties of PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel
[0123] In practical applications, such as wearable devices and flexible sensors, ionic thermoelectric hydrogels are often subjected to tensile deformation. Good tensile properties can ensure that the hydrogel will not easily break or lose function during use, thereby ensuring the stability and reliability of the device. The present invention applies an axial tensile load to the ionic thermoelectric hydrogel sample until the sample breaks, records the relationship between the load and the elongation during the stretching process, and then calculates tensile performance indicators such as tensile strength and elongation at break, thereby evaluating its mechanical properties.
[0124] The specimens were made into uniform, defect-free rectangular strips of 5 cm × 2 cm × 2 mm (length, width, thickness). A tensile testing machine with sufficient accuracy and range was used to apply tensile load at a constant rate (5 mm / min) and accurately measure the load and elongation. A stress-strain curve was drawn based on the recorded data, and the tensile strength and elongation at break were calculated. The tensile strength is the maximum stress when the specimen breaks, and the elongation at break is the percentage of the elongation at specimen break to the original gauge length.
[0125] like Figure 4As shown, the present invention compares the stress-strain curves of different types of ionic thermoelectric hydrogels in Example 1 and the comparative example under the air drying process and the dry annealing process. Among them, the tensile strength of the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel prepared by the dry annealing method in Example 1 reaches 10.3MPa, which is 1.3 times higher than that of the pure PVA hydrogel prepared by the air drying method; the elongation at break after annealing reaches 276%, which is higher than the mechanical properties of most ionic thermoelectric hydrogels at the same thermoelectric level. In addition, the present invention also compares the stress-strain curves of hydrogels with different PFN-Br concentrations under the dry annealing process of Examples 1-4. As the PFN-Br concentration increases, the tensile properties of the hydrogel gradually improve (the performance is best when the PFN-Br concentration is 12.5%, the tensile strength reaches 10.3MPa, and the elongation at break is 276%), and the performance decreases slightly when the concentration is further increased to 15%.
[0126] 2. Thermoelectric performance of PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel
[0127] Ion Seebeck coefficient (S i ) is the most important parameter to measure the thermoelectric performance of ionic thermoelectric materials. When there is a temperature difference between the two ends of the ionic thermoelectric hydrogel, heat diffusion will occur inside the material, resulting in the directional movement of ions, thereby generating a potential difference between the two ends. The ratio of this potential difference to the temperature difference is the ionic Seebeck coefficient S. i。
[0128] In this application, the ionic thermoelectric hydrogel sample is placed between two heat sources with different temperatures, which is usually achieved by using a Peltier patch. The temperature of the two heat sources is adjusted by a temperature controller to ensure that the temperature difference is stable (the temperature difference is 5°C). The electrochemical workstation is connected to the two ends of the hydrogel sample to measure the potential difference generated. When the potential reaches a stable state, the ΔT temperature difference and ΔV potential difference are recorded at this time. According to S i =ΔV / ΔT to calculate the ion thermoelectric potential. In order to improve the measurement accuracy, multiple measurements are performed at different temperature differences and the average value is taken as the final result.
[0129] like Figure 5 As shown in a, the PVA / PFN-Br ionic thermoelectric hydrogel prepared by air drying method has a weak internal hydrophobic interaction, which leads to a low ion mobility under a certain temperature gradient and a small thermoelectric potential. On this basis, copper chloride was introduced and different annealing times were explored. It was found that increasing the annealing time under the synergy of metal coordination and hydrophobic interaction can greatly increase the thermoelectric potential ( Figure 5b), while in the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel prepared in Example 1 of the present invention, as the PFN-Br concentration increases, the thermoelectric potential increases due to the enhanced hydrophobic effect. After the concentration reaches saturation, the thermoelectric potential begins to decrease due to the increased solution viscosity that limits ion movement ( Figure 5 c). After testing different ion concentrations and annealing times, the PVA / CuCl2 / PFN-Br ion thermoelectric hydrogel has a maximum average thermoelectric potential of -21.5 mV / K when dry annealing is performed for 90 minutes based on 0.25 g of copper chloride and 0.625 g of PFN-Br.
[0130] The present application also compares the thermoelectric voltage and mechanical properties of the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel prepared in Example 1 with other different ionic thermoelectric materials, and the results are shown in Table 1. The experimental results show that the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel prepared in Example 1 of the present application has high thermoelectric potential and excellent mechanical properties.
[0131] Table 1 Comparison of thermovoltage and mechanical properties of different ionic thermoelectric materials
[0132]
[0133]
[0134] 3. Application of PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel devices
[0135] like Figure 6 As shown, the present invention evaluates the application of the PVA / CuCl2 / PFN-Br ionic thermoelectric hydrogel device of Example 1. Specific applications include the following aspects: first, after a single ionic hydrogel is connected to an LED via a voltage amplifier, the LED is lit in both stretched and unstretched states under a temperature gradient; second, the modular ionic thermoelectric hydrogel is used as a temperature sensor.
[0136] like Figure 6 As shown in a, first connect the upper and lower ends of the hydrogel to the electrodes, and then establish a connection with the light-emitting diode (LED) through an amplifier. In an environment equipped with a transformer, a temperature difference (temperature difference of 10°C) is applied to the hydrogel with the help of a heating table. At this time, it can be clearly observed that the LED is successfully lit. Then the hydrogel is stretched. During this process, the LED always maintains a luminous state. As the stretching length increases, its brightness shows a trend of gradually decreasing. The ionic thermoelectric hydrogel is then made into a 4×4 array, and the size of each unit is 1×1cm 2Different electrodes were connected to each sensor unit, and then glass bottles containing hot water and cold water (hot water: 40°C, cold water: 10°C) were placed on the sensor array to detect and locate the output voltage signal of each channel, such as Figure 6 As shown in b, the multi-point data processing and mapping functions of external stimuli can be effectively achieved.
[0137] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties, characterized in that: The following steps are involved: S1. Adding a water-soluble conjugated polymer, polyvinyl alcohol and a water-soluble metal salt to deionized water to obtain a mixed solution; wherein the mass ratio of polyvinyl alcohol, water-soluble metal salt and water-soluble conjugated polymer is 1:0.05:0.075~0.15; S2. pouring the mixed solution obtained in step S1 into a mold and subjecting it to freeze-thaw treatment to obtain a freeze-thawed hydrogel; S3. dry annealing the frozen-thawed hydrogel at 80-120°C for 10-110 minutes; S4. The annealed hydrogel is placed in deionized water until fully swollen to obtain an n-type ionic thermoelectric hydrogel.
2. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 1, characterized in that: In step S1, the water-soluble metal salt is selected from one or more of sodium chloride, potassium chloride, copper chloride and zinc chloride.
3. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 2, characterized in that: The water-soluble metal salt is cupric chloride.
4. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 1, characterized in that: In step S1, the water-soluble conjugated polymer is poly(9,9-bis(3'-(N,N dimethyl)-N ethylaminopropyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)).
5. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 1, characterized in that: In step S1, the molecular weight of polyvinyl alcohol is 146,000-186,000.
6. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 1, characterized in that: In step S1, the mass ratio of polyvinyl alcohol, water-soluble metal salt and water-soluble conjugated polymer is 1:0.05:0.
125.
7. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 1, characterized in that: In step S1, a water-soluble conjugated polymer, polyvinyl alcohol and a water-soluble metal salt are added to deionized water, stirred until the water-soluble conjugated polymer and the water-soluble metal salt are completely dissolved, and then stirred and heated in a water bath at 80-120° C. for 8 to 12 hours to obtain a mixed solution.
8. The method for preparing an n-type ionic thermoelectric hydrogel with high thermoelectricity and excellent mechanical properties according to claim 1, characterized in that: In step S2, the freeze-thaw treatment conditions are: freezing at -20 to -40°C for 10 to 14 hours and thawing at room temperature for 10 to 14 hours.
9. An n-type ionic thermoelectric hydrogel prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the n-type ionic thermoelectric hydrogel according to claim 9 in flexible electronic devices.